2016
DOI: 10.9767/bcrec.12.1.557.81-88
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Application of Aluminum Dross as Catalyst in Pyrolysis of Waste Cooking Oil

Abstract: Aluminium dross, a waste material produced by dissolution of aluminum scrap, was characterized physically and chemically by various analysis techniques for a potential to be used as catalyst. Using catalyst from waste materials reduced the cost for synthesizing of new catalyst. An efficient catalyst derived from industrial solid waste was modified by acid washing for using in a pyrolysis of waste cooking oil. The modification of aluminum dross resulted in increased surface area (from 0.96 to 68.24 m 2 /g), aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…The authors identified non-renewable resources that have increased concerns about climate change and environmental complications in the recent years. The production of biodiesel fuel has increased because they are regarded as an effective alternate to fossil fuel-derived transportation fuels [34,44]. The production of biodiesel fuel has shown continuous increase in the recent years due to their potential of fast growth, high oil content and their ability to grow well during unconventional scenarios with inherent carbon neutrality.…”
Section: Recent Progress Of Do Of Realistic Green Oil Worldmentioning
confidence: 99%
“…The authors identified non-renewable resources that have increased concerns about climate change and environmental complications in the recent years. The production of biodiesel fuel has increased because they are regarded as an effective alternate to fossil fuel-derived transportation fuels [34,44]. The production of biodiesel fuel has shown continuous increase in the recent years due to their potential of fast growth, high oil content and their ability to grow well during unconventional scenarios with inherent carbon neutrality.…”
Section: Recent Progress Of Do Of Realistic Green Oil Worldmentioning
confidence: 99%
“…The FT-IR spectra of WCO presented in four extremely broad absorption peak at 2925 cm -1 and 2855 cm -1 , 1746 cm -1 , and 1163 cm -1 which attributed to stretching absorption of C-H bond attached to the carbon atom in the palmitic acid and oleic acid, absorption of glyceride carbonyl group (C=O) and C-O group from ester bond, respectively. The summary of IR absorption characteristic for pyrolysis oil is presented in Table 6 [11,23,24].…”
Section: Functional Group Analysismentioning
confidence: 99%
“…Direct applications as raw materials in the refractory brick [16] or in the production of inert filling for construction, road paving, mortar components, polymer composites, adsorbents, and mineral wood have been reported [17]. While other researchers have aimed to use them to manufacture other raw materials such as hydrogen gas [18], X-zeolites [19], aluminum sulfate (Al2(SO4)3.18H2O) [20] and alumina with different properties for many applications like catalysis [21,22], cement [23], biomaterials [24] and refractory [16].…”
Section: Introductionmentioning
confidence: 99%